Biochar, compost and biochar-compost blend as options to recover nutrients and sequester carbon. (15th July 2018) - Oldfield, Thomas L.; Sikirica, Nataša; Mondini, Claudio; López, Guadalupe; Kuikman, Peter J.; Holden, Nicholas M.
Abstract: This work assessed the potential environmental impact of recycling organic materials in agriculture via pyrolysis (biochar) and composting (compost), as well its combination (biochar-compost blend) versus business-as-usual represented by mineral fertiliser. Life cycle assessment methodology was applied using data sourced from experiments (FP7 project Fertiplus) in three countries (Spain, Italy and Belgium), and considering three environmental impact categories, (i) global warming; (ii) acidification and (iii) eutrophication. The novelty of this analysis is the inclusion of the biochar-compost blend with a focus on multiple European countries, and the inclusion of the acidification and eutrophication impact categories. Biochar, compost and biochar-compost blend all resulted in lower environmental impacts than mineral fertiliser from a systems perspective. Regional differences were found between biochar, compost and biochar-compost blend. The biochar-compost blend offered benefits related to available nutrients and sequestered C. It also produced yields of similar magnitude to mineral fertiliser, which makes its acceptance by farmers more likely whilst reducing environmental impacts. However, careful consideration of feedstock is required. Highlights: From a C-sequestration perspective, biochar, compost and blend are favourable in agriculture. From a nutrient recovery perspective, compost and blend are beneficial in agriculture. No agricultural system resulted in the lowest environmental impact for all categories included. From a grave-to-cradle perspective, the blending of compost and biochar is favourable. Choice of functional unit and system boundary is challenging for agricultural systems.